Pensioners’ Poverty Requires Fundamental Reform - Ernst Niemeier (Wirtschaftsdienst)
Abstract The German government seeks to improve the situation of longterm pension contributors with the basic pension (“Grundrente”). However, the basic pension only combats the symptoms rather than addressing the causes of low pensions and old age poverty: the policy of low wages and wrong macro economic policy. The political responsibility of these pension problems require taxfinanced compensations to guarantee a subsistence level.